2020
DOI: 10.1097/aln.0000000000003061
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Thromboelastography with Apparent Rivaroxaban Concentration

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Concern remains over reliable point-of-care testing to guide reversal of rivaroxaban, a commonly used factor Xa inhibitor, in high-acuity settings. Thromboelastography (TEG), a point-of-care viscoelastic assay, may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…More recently, commercially produced reagents for the ROTEM and TEG® 6S platforms have been utilized to provide qualitative assessment of direct oral anticoagulant effects. 62,63 Similarly, the ecarin clotting assay and the Russel viper venom test have been used on the ClotPro platform to assess plasma concentrations of dabigatran and factor Xa inhibitors, respectively. 64,65 These may eventually allow perioperative physicians to follow reversal of oral DTIs and factor Xa inhibitors, as doing so with currently available testing options is not recommended.…”
Section: Point-of-care Testingmentioning
confidence: 99%
“…More recently, commercially produced reagents for the ROTEM and TEG® 6S platforms have been utilized to provide qualitative assessment of direct oral anticoagulant effects. 62,63 Similarly, the ecarin clotting assay and the Russel viper venom test have been used on the ClotPro platform to assess plasma concentrations of dabigatran and factor Xa inhibitors, respectively. 64,65 These may eventually allow perioperative physicians to follow reversal of oral DTIs and factor Xa inhibitors, as doing so with currently available testing options is not recommended.…”
Section: Point-of-care Testingmentioning
confidence: 99%
“…Thirteen studies described rivaroxaban action in whole blood with TEG (Haemonetics Corporation, Boston MA, U.S.A.) ( 20 22 , 25 , 26 , 31 – 33 , 35 , 37 , 42 , 43 , 46 ) ( Supplementary Table 2.2 ). Of these, four studies did not report the exact rivaroxaban concentration under which conditions the viscoelastic tests were performed ( 22 , 25 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant correlation between rivaroxaban plasma concentration and reaction time (R) have been reported for the specific anti-factor-Xa channel [AFXa] (strong to very strong correlation) ( 20 , 21 , 37 ), and for citrated kaolin channel (moderate to strong correlation) ( 35 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…In ROTEM, we expect a prolonged clotting time in the extrinsically activated thromboelastometry (EXTEM) assay that is related to the Xa inhibitor's plasma concentration, 9 and in thrombelastography a prolonged reaction time. 10 Although typical major trauma patients were absent in the mentioned andexanet alfa studies, [4][5][6] reversal of anticoagulation may be indicated in such patients. It is unlikely that one single drug will ever be the "magic bullet" of coagulation management.…”
Section: "What Are the Issues Facing Clinicians Who Manage Bleeding P...mentioning
confidence: 99%